Inverse interpolation applied to temporal transient response characteristics to parameters of the typical second order transfer function - Javier Joglar Alcubilla (Revista Iberoamericana de Automática e Informática Industrial RIAI)
In order to obtain a method of temporary specification translation to the frequency domain, which minimizes overdesign and manual iteration in the process of searching for a controller in frequency, it is proposed to use successive approximations automatically, applying any inverse interpolation. In this regard, specific techniques are recommended to obtain specification translation for each type of requirement, based on the “ascending and descending differences Newton method of 5th order” due to its practice advantages, compared to other interpolation procedures. For this, it will be used as interpolation functions those describing step signal or pulse signal, with subcritical damping and approached with a second order model.